Theoretical Principles of Studying Borrowings in Different Types of Discourse - Нестеренко, Діна Юріївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article is devoted to studying the problems of borrowing foreign elements and their functioning in the modern Ukrainian language. The questions of their discursive adaptation are also covered. Among the main aspects of the analysis the problem of defining the term “borrowing” and its interpretation is a crucial one. Special attention is paid to the analysis of extralingual and intralingual factors that influence penetration of the borrowed elements into the language. The attempt to retrace the evolution and variation of the factors mentioned above through the prism of synchrony and diachrony as well as depending on the type of a discourse was made.